Search for the associated production of charm quarks and a Higgs boson decaying into a photon pair with the ATLAS detector - Aad, Georges; Ackermann, Anke; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; Sanfilippo, Lorenzo; et al. (Journal of high energy physics, 2025)
A search for the production of a Higgs boson and one or more charm quarks, in which the Higgs boson decays into a photon pair, is presented. This search uses proton-proton collision data with a centre-of-mass energy of √s= 13 TeV and an integrated luminosity of 140 fb−1 recorded by the ATLAS detector at the Large Hadron Collider. The analysis relies on the identification of charm-quark-containing jets, and adopts an approach based on Gaussian process regression to model the non-resonant di-photon background. The observed (expected, assuming the Standard Model signal) upper limit at the 95% confidence level on the cross-section for producing a Higgs boson and at least one charm-quark-containing jet that passes a fiducial selection is found to be 10.6 pb (8.8 pb). The observed (expected) measured cross-section for this process is 5.3 ± 3.2 pb (2.9 ± 3.1 pb).
The ATLAS Collaboration: G. Aad, A. Ackermann, L.M. Baltes, F. Bartels, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, L. Sanfilippo, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser und weitere 2917
Gesehen am 17.10.2025